2022
DOI: 10.3390/jof9010023
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pneumocystis jirovecii Pneumonia among Solid Organ Transplant Recipients: A Population-Based Study

Abstract: Few studies have comprehensively investigated the occurrence of Pneumocystis jirovecii pneumonia (PJP) among solid organ transplant (SOT) recipients. This study investigated the risk of PJP after organ transplantation. Each patient who underwent SOT was propensity-score-matched with four non-SOT individuals in terms of sex, age, insured salary, urbanization of residence, comorbidities, and year of enrollment. When considering the 3-year follow-up, the patients who had undergone SOT were at higher risk of PJP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…There is a single case--control study in heart transplant recipients demonstrating improved mortality outcomes with combination therapy (20%) compared to TMP/SMX monotherapy (33.3%) [57]. The novel antifungal agent, ibrexafungerp, has also been shown to have activity against Pneumocystis in animal models [58].…”
Section: Treatmentmentioning
confidence: 99%
“…There is a single case--control study in heart transplant recipients demonstrating improved mortality outcomes with combination therapy (20%) compared to TMP/SMX monotherapy (33.3%) [57]. The novel antifungal agent, ibrexafungerp, has also been shown to have activity against Pneumocystis in animal models [58].…”
Section: Treatmentmentioning
confidence: 99%
“…However, with these prophylactic measures, people found that the peak of PJP occurrence changed and was postponed. PJP can occur rather late after organ transplantation 13,14 . Then, in 2019, The American Society of Transplantation recommended prophylaxis with daily or double doses of three times weekly TMP‐SMX for 6–12 months 15 …”
Section: Introductionmentioning
confidence: 99%
“…PJP can occur rather late after organ transplantation. 13,14 Then, in 2019, The American Society of Transplantation recommended prophylaxis with daily or double doses of three times weekly TMP-SMX for 6-12 months. 15 To avoid PJP, the risk factors should be identified and prevented if possible.…”
Section: Introductionmentioning
confidence: 99%
“…Organ dysfunction is associated with pronounced adverse effects on skeletal integrity, as evidenced by marked decreases in bone mineral density (BMD), deterioration of microstructural quality, and a consequent reduction in biomechanical strength, cumulatively increasing the risk of osteoporotic fractures even before transplantation [8]. The most precipitous decline in BMD typically occurs within the first 6 to 12 months following transplantation, marked by a striking surge in fracture risk [9,10]. Recent research underscores the gravity of this issue, revealing that the hazard ratio for osteoporosis after solid organ transplantation is approximately five times higher than that for non-transplant patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most precipitous decline in BMD typically occurs within the first 6 to 12 months following transplantation, marked by a striking surge in fracture risk [9,10]. Recent research underscores the gravity of this issue, revealing that the hazard ratio for osteoporosis after solid organ transplantation is approximately five times higher than that for non-transplant patients [9]. Several key risk factors contribute to the development of transplantation osteoporosis, with pre-transplant bone disease and post-transplant immunosuppressive therapy emerging as the primary culprit [7,11,12].…”
Section: Introductionmentioning
confidence: 99%